Numerical simulation and experimental validation of a wind turbine using Generative Design - Grardel, Martin; Tokam, Cabrel Kengne; Denis, Maxime; Bain, Olivier; Dujany, Arnaud (Computer Aided Chemical Engineering, 2024)
With an energy demand in continuous growth over the last decade and new climate change stakes, ways to create more power has been studied. Offshore winds turbine which creates energy out of the wind was thus studied. Many studies have been led about the optimization stake that wind turbine are facing as actually, more than half of the wind power is lost when exploited by a classic horizontal wind turbine (HAWT). A particular new technology is now used in industry and can be applied to this problematic: Generative Design. It refers to all the numerical conception methods that automatically perform a design exploration with constraints defined by the user. To evaluate the relevance of this new conception methods on this subject, it was decided to create two prototypes of blades using two Generative Design applications of CATIA, a computer aided design (CAD) software. The first application (called XGenerative Design) has permitted to create a simple blade design only by using 3D parametric modelling, which make the process easier than creating it with actual means, those requiring precision and time. The second application (called Parametric Design Study) has permitted to ameliorate this previous blade design by implementing parametric ameliorations, a method of topology optimization. Two blades were tested: the blade created on XGenerative Design and a second similar blade model, but this time optimized with topology optimization. The blades were assembled on two separate classic wind turbine models and were evaluated in the fluid dynamic simulation software XFlow under an equivalent wind. The results proved that the optimized model with parametric ameliorations has a slightly better rotation speed than the non-optimized one. However, as these technologies are very recent, it wasn’t possible to fully ameliorate the initial design. It was planned to ameliorate it by using mechanical evaluations methods of the blades. It seems that this conception method still needs some improvement in the future, even if in some other domains, it has already proved his efficiency.